PENGARUH ONLINE CUSTOMER REVIEW, ONLINE CUSTOMER RATING, E-SERVICE QUALITY DAN PRICE TERHADAP KEPUTUSAN PEMBELIAN PADA MARKETPLACE SHOPEE (STUDI KASUS PADA MAHASISWA UNIVERSITAS MUHAMMADIYAH SURAKARTA) - Afifah Rizky Putri; Wuryaningsih Dwi Lestari (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to analyze the influence of online customer reviews, online customer ratings, e-service quality and prices on purchasing decisions in the Shopee marketplace. The type of research used in this research is quantitative. The population and sample of this study were students of Muhammadiyah University of Surakarta who made purchasing decisions in the Shopee marketplace, the number of samples was 118 respondents. The type of data used is primary data. Methods of data collection using a questionnaire. Data analysis used multiple linear regression analysis using SPSS version 25. The results of the analysis in this study indicate online customer reviews have a positive and significant effect on purchasing decisions, online customer ratings have a positive and significant effect on purchasing decisions, e-service quality has a positive and significant effect on purchasing decisions. purchasing decisions, and prices have a positive and significant effect on purchasing decisions.